JENIS KALIMAT IMPERATIF BAHASA JAWA PADA SYI’IR NGUDI SUSILO KARYA K.H. BISRI MUSTOFA - Endah Normawati Mahanani; Suroto Rosyd Setyanto; Ahmad Pramudiyanto (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The title of this research is “The Kind of Javanese Imperative Sentences in Ngudi Susilo Poem By K.H. Bisri Mustofa,, while the purposes of the research is to know what kind of imperative sentence contained in  Syi’ir Ngudi Susilo by K.H. Bisri Mustofa.. This research uses qualitative methode. The data resource in this research is the book entitled Ngudi Susilo poem by K.H. Bisri Mustofa, while the data is imperative sentence.  The result of this thesis include : 1) Imperative senteces based on formal form, consisting of : (a) polite imperatif sentences: with the suffix marker –ana ‘lah’ an the suffix marker –ake ‘kan’; (b) transitive imperative sentences with declarative contructions; (c) intransitive imperative sentences with declarative constructions; and 2) imperative sentences based on lexical markers, consisting of: (a) impeative sentences of necessity marked by the modality kudu ‘must’+verb, kudu ‘must’+adjective, kudu ‘must’+noun; (b) imperative sentences of prohibition markes by aja ‘don’t’+verb, aja ‘don’t’+adjective, aja ‘don’t’+noun; (c) combined imperative senetences with markers: kudu ‘must’ (...)+aja ‘don’t’ (...) and the suffix –ana ‘lah’+ -aja ‘don’t’.